Perkawinan di Tengah Krisis Ekonomi: Antara Mimpi dan Kenyataan dalam Perspektif Pendidikan Agama Islam - Andira Indran Arum; Tri Rahayu; Nofia Puspita Salsabila; Novi Indriyanti; Dinar Widayanti; Monik Yulida Setyowati; Syifa Hanadila (Pusat Riset dan Inovasi Nasional, 2025)
Marriage is the union of two indivoduals in legal bond. In the Islamic perspective, marriage is not only a covenant between two people, but also a sunatullah or Allah’s decree that applies to all of Allah’s creatures. This research analyzes marriage in the midst of an economic crisis from the persperctive of Islamic Religious Education, focusing on the concept of marriage, the impact of the economic crisis, the role of Islamic Religious Education, Islamic solutions to the challeges of marriage in the midst of an economic crisis. This research uses a qualitative method with literature analysis with the aim of describing the discussion of marriage and the economy